6t+3=5t+8

Simple and best practice solution for 6t+3=5t+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+3=5t+8 equation:


t in (-oo:+oo)

6*t+3 = 5*t+8 // - 5*t+8

6*t-(5*t)-8+3 = 0

6*t-5*t-8+3 = 0

t-5 = 0 // + 5

t = 5

t = 5

See similar equations:

| a+2=-4a-58 | | k+8=-12+6k | | 3X^2-21x+18=0 | | 2x+7x-90=180 | | 7+5t=7t+1 | | 2m-10=-6+4m | | 2k-1=7k-21 | | 2n-10=-7n-1 | | 2(x+6)-10=12 | | 9+5n=4n-2 | | 5m-1=11+m | | 2a-1=-31+7a | | 12/2(1+2) | | 4x-5=-9+6x | | 10-6d=-2d-10 | | -7-4b=-3b+0 | | -2n-3=3n-43 | | 4w-3=-3-6w | | 4+6d=-4d+64 | | -16-18=3 | | 5w-7=2w-7 | | 6b-6=7b-16 | | 5m+3=23-5m | | -5k+10=16-3k | | 3-5a=3a+11 | | -7x+9=7-6x | | -7-4x=5x-115 | | 2x+9=31-2x | | x^2-3/2x-23/16=0 | | 5d-6=-20+7d | | 3d-2=6d+19 | | -7m+3=2m-42 |

Equations solver categories